Penipuan (Ghisy) dalam Jual Beli: Analisis Hadis tentang Etika Perdagangan Islam - Reski Eka Putri; Muhammadiyah Amin; Abdul Rahman Sakka (STAI DDI Kota Makassar, 2026)
This study examines the practice of fraud (ghisy) in buying and selling transactions within traditional markets and online marketplaces. Ghisy, linguistically meaning deception or concealing defects, is strictly prohibited in Islam as affirmed by the Prophet Muhammad's saying: